AUTEKOLOGI NEPENTHES PITOPANGII LEE.DI KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - M. Saleh, Muhammad Fajrri Ramadhan; Miswan, Miswan; Pitopang, Ramdanil (Natural Science: Journal of Science and Technology, 2013)
The growth and development of Nepenthes are affected by abiotic and biotic factors in its environment. In this study, to measure and to identify the abiotic and biotic factors surrounding the Nepenthes pitopangii Lee.naturally grow in the Lore Lindu National Park (LLNP) in Central Sulawesi.  The measurement of abiotic factor and the identification of biotic factor have been carried out from April to May 2013. The abiotic factors such as temperature and relative humidity were measured with thermometer and pscychrometer respectively. While, the precipitation data were obtained from Badan Meteorologi dan Geofisika Palu. Nitrogen and phosphorus concentrations of soil where N. pitopangii Lee grow were measured with metode khcelhal dan metode Bray-1.The plants which compose vegetation in the surrounding of Nepenthespitopangii Lee.were analyzed with systemic double plot method and than they were identified. The animals that affect Nepenthespitopangii Lee.growth were also identified. The results showed that in the LLNP, daily temperature, relative humidity and precipitation that affect Nepenthespitopangii Lee. growth were 17.1 °C, 90.2% and 313.3 mm respectively. Nepenthespitopangii Lee.can grow in the very low soil N and P concentrations. At tree level, vegetation was dominated by Helicia celebica Sleumer with importance value index (IVI) of 69.94%. Eurya accuminata DC. (IVI 59.92%) dominated vegetation at pole level, Xanthomyirtus angustifolius Scoot. (IVI 74.57%) dominated vegetation at sapling level, and Gleichenia truncata (IVI 44.43%) dominated vegetation at seedling level.  The wild animals are found in the study area to interacting directy on Nepenthes pitopangii Lee. inPolyrachis Sp, Camponotus Sp, Apidae Sp